THE ROLE OF THE SCIENTIFIC HERITAGE LEFT BY OUR ANCESTORS IN THE FORMATION OF THE SPIRITUAL WORLD VIEW OF THE YOUT (American Journal of Research in Humanities and Social Sciences, 2024)
This article highlights the important role of the scientific heritage of Uzbekistan in the formation of the spiritual worldview of young people. It explains how the intellectual heritage left by ancestors affects the values, beliefs and worldview of young people in modern Uzbek society. The article further emphasizes the influence of this heritage on the formation of identity and cultural consciousness in young people through the study of historical, literary, philosophical and cultural works.